Nilai-Nilai Pendidikan Karakter dalam Film Animasi “NUSSA” dan Relevansinya dengan Pendidikan Agama Islam - Qulud Rizki Triandari; Yoga Sari Prabowo (Journal on Education, 2024)
This research aims to identify the values of character education in the animated film Nussa and their relevance to Islamic Religious Education at SDN I Sukoharjo Bandung. A qualitative approach was used by collecting data through content analysis and observation of the film Nussa. The research results show that the Nussa film contains several positive character education values, such as obedience to Allah, polite speech, honesty, justice, kindness, and concern for the environment. These values are relevant to Islamic teachings and can be a source of inspiration for children in developing themselves. Apart from that, the film Nussa also depicts local religious and cultural practices, such as midday prayers, covering the intimate parts, and shaking hands with teachers, which reflect Islamic values and culture at SDN I Sukoharjo Bandung. Thus, the animated film Nussa can be an effective tool in teaching character values to children at the school. It is hoped that teachers can use this film as a learning resource that is interesting and relevant to the values they teach at school.